A Selection Rule for Hydrofluoroether Electrolyte Cosolvent: Establishing a Linear Free‐Energy Relationship in Lithium–Sulfur Batteries. (27th June 2019) - Su, Chi‐Cheung; He, Meinan; Amine, Rachid; Amine, Khalil
Abstract: Hydrofluoroethers (HFEs) have been adopted widely as electrolyte cosolvents for battery systems because of their unique low solvating behavior. The electrolyte is currently utilized in lithium‐ion, lithium–sulfur, lithium–air, and sodium‐ion batteries. By evaluating the relative solvating power of different HFEs with distinct structural features, and considering the shuttle factor displayed by electrolytes that employ HFE cosolvents, we have established the quantitative structure–activity relationship between the organic structure and the electrochemical performance of the HFEs. Moreover, we have established the linear free‐energy relationship between the structural properties of the electrolyte cosolvents and the polysulfide shuttle effect in lithium–sulfur batteries. These findings provide valuable mechanistic insight into the polysulfide shuttle effect in lithium–sulfur batteries, and are instructive when it comes to selecting the most suitable HFE electrolyte cosolvent for different battery systems. Abstract : Hochleistungsbatterien erfordern maßgeschneiderte Elektrolyte als Lösungsmittel. Die Lithium‐Lösungsfähigkeit einer Reihe von Hydrofluorethern (HFEs) und die lineare Freie‐Energie‐Beziehung zwischen diesen Lösungsmitteln und Lithiumpolysulfid (LiPS) wurden ermittelt. Die HFE‐Strukturen (A, B und C) variieren in Bezug auf die Lage der Fluoralkylgruppen und einem Ethersauerstoffatom. Schlüssel: Lithium‐Solvatationskraft (1), Leitfähigkeit (2), LiPS‐Auflösung (3).